2012
DOI: 10.1074/jbc.m111.322669
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA Sequencing Reveals MicroRNAs That Modulate Angiotensin II Effects in Vascular Smooth Muscle Cells

Abstract: Background: Role of microRNAs in angiotensin II-mediated vascular smooth muscle cell (VSMC) dysfunction is unclear. Results: Angiotensin II up-regulates miR-132 in VSMC. miR-132 induces MCP-1 partly via targeting PTEN, activates CREB, and regulates genes related to cell-cycle and motility. Conclusion: miR-132/212 is a novel modulator of Ang II actions. Significance: miRNAs may serve as new drug targets for Ang II-mediated cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
73
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 58 publications
4
73
0
Order By: Relevance
“…Aortic VSMC were isolated from 10–12 weeks old type 2 diabetic db/db mice and control db/+ mice (Jackson laboratories, Bar Harbor, ME) and cultured as described 12, 33 . RNA extraction and gene expression analysis were performed by quantitative Realtime PCR (RT-qPCR) 28, 33 . Small RNA-seq (smRNA-seq) was performed once, with one sample per group using Illumina protocols.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aortic VSMC were isolated from 10–12 weeks old type 2 diabetic db/db mice and control db/+ mice (Jackson laboratories, Bar Harbor, ME) and cultured as described 12, 33 . RNA extraction and gene expression analysis were performed by quantitative Realtime PCR (RT-qPCR) 28, 33 . Small RNA-seq (smRNA-seq) was performed once, with one sample per group using Illumina protocols.…”
Section: Methodsmentioning
confidence: 99%
“…SI). Transient transfection of VSMC, immunoblotting, luciferase assays, cell proliferation and migration assays were performed as described earlier with some modifications 28, 33 . All the experiments were repeated at least twice with replicates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the biology of the glomerular compartment is heavily influenced by the renin-angiotensin system (RAS) that regulates local intrarenal hemodynamics, which apparently worsens the pathological outcome of a given glomerular disease. Prime examples where the activation of the RAS or ANG II contributes to or amplifies the injury are diabetic nephropathy and cardiovascular smooth cell dysfunctions, as reported in several studies, reviews, and perspectives (13,24,35,49,62,70). In any event, it is conceivable that the activation of the RAS besides causing perturbation in the glomerular compartment may also modulate the tubulointerstitial injury since some of the RAS components are believed to be expressed within this compartment (33,37).…”
mentioning
confidence: 99%
“…They found that miR-195 (alone of the miR-15 family) was increased in aneurysmal aortic tissue from Angiotensin II(AngII)-treated apoE−/− mice. AngII has previously been shown to induce or inhibit miR-15a, -15b, -16-1 and -16-2 in either rat or human smooth muscle cells (SMC), but not miR-195 10, 11 . Further, while significant downregulation of miR-15a, miR-195 and miR-497 has been observed in tissue from dissected human thoracic aorta when compared with normal aorta, Pahl et al’s expression profiling of human AAA tissue did not identify any differentially regulated miR-15 family members 12, 13 .…”
mentioning
confidence: 99%